Influences of gallium substitution on the phase stability, mechanical strength and cellular response of β-tricalcium phosphate bioceramics. Issue 10 (July 2020) - Qiu, Chao; Lu, Teliang; He, Fupo; Feng, Songheng; Fang, Xibo; Zuo, Fei; Jiang, Qiangguo; Deng, Xin; Ye, Jiandong
Abstract: β-tricalcium phosphate (β-TCP), a well-accepted synthetic bone grafting biomaterial, is confronted with limitations of poor phase stability and lacking the capacity to mediate the biological functions. In the current study, gallium (Ga) was substituted for calcium in the β-TCP, and the influences of Ga substitution on the phase stability, compressive strength and cellular response of β-TCP bioceramics were investigated. The results indicated that substitution of at least 2.5 mol% Ga for calcium prevented the β-TCP from transforming into α-TCP at 1250 °C. The β-TCP bioceramics substituted with 2.5 mol% Ga attained the highest compressive strength. The β-TCP bioceramics substituted with 2.5 and 5 mol% Ga showed good cytocompatibility, and suppressed in vitro osteoclastic activity as well as osteoblastic differentiation. Considering the favorable mechanical strength and the inhibitory effect on the osteoclastic activity, the β-TCP bioceramics substituted with 2.5 mol% Ga are promising for treating the bone defect in the pathological state of excessively rapid bone resorption.